Brooke Bennett's Full Stroke at 560 m of Her 800 m Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S.
Video pictures (20 frames) and the appropriate technical/ biomechanical explanations for Brooke Bennett's full stroke at 560 m of her 800 m gold medal race at the Atlanta Olympic Games 1996.